Types of characterizations of the main character in the “friends with benefits” film - Somanasih, Kadek; Resen, I Wayan; Juniartha, I Wayan (Journal of Language and Applied Linguistics, 2021)
The film Friends with Benefits is the data source in this study. In collecting the data through library research by viewing films, reading scripts, and taking notes. In analyzing the data, the qualitative method is used and presented descriptively based on the theory adopted in this study. The theory used in this study is the theory of literature proposed by Wellek and Warren (1949) about characterization. The results of this study showed that only three characterization dimensions were analyzed. In presenting these dimensions, this study presents an overview and/or dialogue from the film. There are three dimensions of the characterization of the main character analyzed in this study: physiological, sociological, and psychological. These physical and psychological characteristics combine to build up Jamie Rellis and Dylan Harper, a romantic person in the film Friends with Benefits.